Staging a Boycott: Photographs of the Nazi Attack on Jewish-Owned Businesses in April 1933 - Kreutzmüller, Christoph (Holocaust and genocide studies, 2024)
On April 1, 1933, the Nazi regime staged the brutal state-organized blockade of Jewish-owned businesses as a peaceful boycott. At the time, attempts to influence public opinion only worked to a limited extent. Both domestic and international papers were reluctant to print photos that represented the Nazi perspective too clearly. Yet astonishingly, the Nazi perspective prevails today. The photos made by the Nazis and their helpers to stage the "boycott" are dominant in exhibitions and publications. The "Nazi victory on the shopfront," as The Guardian called it in 1933, has therefore turned into a belated victory on the "photo front." This article analyzes the photos taken on April 1, 1933, deconstructs the propaganda messages embedded in them, and reconstructs the violence of the Nazi regime’s first systematic assault against the Jews in Germany.